Caffeine intake and awareness of its adverse effects: Insights from the medical students at the University of Tabuk - Omnia S. El Seifi; Faten Ezzelarab Younis; Nouf Ali Alsaiari; Rama Mathel Alanazi; Atheer Khalaf Alanazi; Lama Mana Alamri; Mona Salem Albalawi; Shahad Hammad Alatawi; Eman M. Mortada (PLoS ONE, 2025)
Background/Objectives Medical students may consume more caffeine-containing beverages to cope with their stressors, resulting in negative effects on physical or mental well-being. This study aimed to determine the prevalence of caffeine use among medical students as well as their awareness of the negative consequences of caffeine use and its implications on mental health. Methods 305 medical students participated in this cross-sectional study. An online self-administered questionnaire was provided, which included sociodemographic data, caffeine intake patterns, caffeine side effects, and the World Health Organization’s Five Well-Being Index to measure mental health. Results 81.3% of the medical students reported consuming caffeine. Of them, 52% consumed ≥ 400 mg of caffeine per day despite 73.1% of them being adequately aware of its negative consequences. The percentage of medical students who reported some negative effects from caffeine use was 80.6%. Being male (OR: 10.6) and consuming caffeine for several reasons, such as enhancing academic achievement (OR: 8.4), staying awake (OR: 6.5), as a habit (OR: 4.6), or elevating mood (OR: 3.0), all significantly associated with high caffeine intake. On the other hand, being highly aware of its side effects is protective (OR: 0.69). Furthermore, there was a strong inverse correlation between the mental well-being score and caffeine consumption (r = −0.563, P < 0.001). Conclusions Because caffeine consumption is remarkably prevalent among the studied medical students, and one-third of those who consumed a lot of caffeine had poor mental well-being, preventive intervention programs need to be implemented to lower their caffeine consumption.